2020
DOI: 10.1093/ajhp/zxaa128
|View full text |Cite
|
Sign up to set email alerts
|

Towards precision medicine: Therapeutic drug monitoring–guided dosing of vancomycin and β-lactam antibiotics to maximize effectiveness and minimize toxicity

Abstract: Abstract Purpose The goal of this review is to explore the role of antimicrobial therapeutic drug monitoring (TDM), especially in critically ill, obese, and older adults, with a specific focus on β-lactams and vancomycin. Summary The continued rise of antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 68 publications
0
52
0
Order By: Relevance
“…However, previous work has established that the precision and bias for AUC estimation is within clinically acceptable limits. 38,39 Furthermore, while it is acknowledged that this surrogate measure requires further confirmation, particularly with respect to the upper toxicity threshold, 40 this study demonstrated a significant reduction in the length of vancomycin therapy following Service implementation, which may reflect a decreased time to infection resolution. Of note, this change occurred in the context of a simultaneous 27% relative reduction in the proportion of AUC 24 values exceeding the toxicity threshold.…”
Section: Articlementioning
confidence: 75%
“…However, previous work has established that the precision and bias for AUC estimation is within clinically acceptable limits. 38,39 Furthermore, while it is acknowledged that this surrogate measure requires further confirmation, particularly with respect to the upper toxicity threshold, 40 this study demonstrated a significant reduction in the length of vancomycin therapy following Service implementation, which may reflect a decreased time to infection resolution. Of note, this change occurred in the context of a simultaneous 27% relative reduction in the proportion of AUC 24 values exceeding the toxicity threshold.…”
Section: Articlementioning
confidence: 75%
“…The importance of TDM in maximizing antimicrobial effectiveness and decreasing adverse events has been emphasized also for additional populations with altered PK, e.g., obese, elderly, pregnant, or burns patients, as well as patients with difficult-to-treat bone infections. 76,86…”
Section: Beta-lactamsmentioning
confidence: 99%
“…Still, there are a number of other drugs well-positioned for MIPD that could benefit from the continuous learning strategy presented here. 24,25 There appears to be limited gains in predictive performance from fitting a continuous learning model on > 200 patients, with the models fit on 350 patients and 200 patients performing similarly in prediction error and bias. Consistent with this finding, the models from the literature trained on at least 200 patients (Avedissian: 250, Colin: 2,554, and Kloprogge: 616) generally showed better predictive performance than those of models fit on fewer than 200 patients (Lamarre: 78, and Le: 138).…”
Section: Discussionmentioning
confidence: 99%
“…For these applications, continuous learning may need to be expanded to include a systematic covariate selection process. Still, there are a number of other drugs well‐positioned for MIPD that could benefit from the continuous learning strategy presented here 24,25 …”
Section: Discussionmentioning
confidence: 99%